Effects of government interventions on bank performance - Soňa Sivá (Charles University in Prague, Institute of Economic Studies (IES), 2023)
This paper evaluates the effects of government bailout policies on bank performance in the EU banking sector. Using a unique dataset of government supports, I identify banks which received state support in years 2008-2014 and corresponding control group of banks. I apply difference-in-differences method and extend it by propensity score matching and inverse probability of weighting methods to account for non-randomness of a treatment. My results suggest that aided banks overtook non-aided ones in terms of lending activity in both, the EU Core and EU Periphery, but it was accompanied by increased non-performing loans ratio (NPL) in the EU Periphery. Finally, I show these results differ from the developments in the US. TARP recipients improved their capital adequacy compared to non-intervened banks and returned to pre-crisis level in terms of NPL and profitability.
Keywords: G21; G28; 330; bailout; financial crisis; bank performance